Assessment of Children's Sociocognitive Abilities Using the ESB Test Battery: a Pilot Study - Katarína Metesová; Svetlana Kapalková; Henrieta Kučesová (Listy klinicke logopedie)
Impaired sociocognitive abilities may signal the risk of a social (pragmatic) communication disorder or Autism Spectrum Disorder. Early identification of difficulties is crucial for initiating targeted intervention and preventing the escalation of existing deficits. The aim of this paper is to introduce the foreign diagnostic tool, the Early Sociocognitive Battery (ESB), developed by Shula Chiat, Penny Roy and Jennifer Warwick. This tool enables direct assessment of children's sociocognitive abilities at an early age. The theoretical description of the ESB is supplemented by a brief overview of the results from the pilot testing of 44 typically developing Slovak-speaking children in the younger preschool age group, focusing on the analysis of children's performance in relation to gender. Participants were assessed using the ESB, Nonword Repetition Task, and Language Use Inventory (LUI). Pilot data show that the children's gender does not have a significant impact on their performance within the ESB tool. In addition, a statistically significant correlation was found between the total score on the LUI and the score on the Joint Attention subtest of the ESB. The results support the applicability of the ESB tool in the Slovak cultural and linguistic context.